Bad boys, good girls? Implicit and explicit attitudes toward ethnic minority students among elementary and secondary school teachers. (June 2017) - Glock, Sabine; Klapproth, Florian
Highlights: Implicit and explicit attitudes toward ethnic minority students were assessed. We compared elementary and secondary school teachers' attitudes. We assessed attitudes toward boys and girls. Elementary school teachers' were implicitly more negative toward boys. Secondary school teachers implicitly favored boys. Abstract: Teachers' attitudes toward ethnic minority students might differ by students' gender and the type of school teachers are working in because of different motivations for teaching and different school practices. Hence, the aim of the current research was to investigate elementary ( n = 82) and secondary school ( n = 82) teachers' implicit and explicit attitudes toward male and female ethnic minority students. Teachers worked on either a male or a female Implicit Association Test and filled out a gender-specific questionnaire for measuring explicit attitudes. The results showed that elementary and secondary school teachers had negative implicit attitudes toward ethnic minority students, independent of students' gender. Whereas secondary school teachers were implicitly more positive toward boys, elementary school teachers were implicitly more positive toward girls. Elementary school teachers were more enthusiastic about teaching ethnic minority boys than girls. The findings provide the first insights into differences in attitudes between elementary and secondary school teachers.